Passive Rule-Based Approach To Detect Sinkhole Attack In 6lowpan Rpl Based Internet Of Things Networks - Subh, Al Sarawi Shadi Mustafa (2024)
The aim of this thesis is to propose a Passive Rule-Based Approach named PRBA to detect sinkhole attacks in 6LoWPAN RPL-based IoT Networks, which consists of four stages to achieve four research objectives, which are: (1) Data collection and preprocessing stage that fulfills the objective to transform the collected power consumption values and the captured ICMPv6 network traffic into a meaningful format; (2) Feature Selection stage that fulfills the objective to decrease the size of the features by selecting the most significant features that contribute to detecting sinkhole attacks; (3) Behavioral Indicators stage that fulfills the objective to identify abnormal behavior of sinkhole attacks using the features of the ICMPv6 and power consumption from the previous stage; and (4) Sinkhole Attack Detection stage that fulfills the objective to decide whether there is a sinkhole attack in two steps.